WORK ETHOS REVIEW FROM WORK CULTURE,WORK ENVIRONMENT AND LEADERSHIP (CASE STUDY AT PT. CAHAYA BUMI NASIONAL SURAKARTA) - Astari Damayanti; Sri Hartono; Istiqomah Istiqomah (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
A running company must have a purpose. In making it happen, a company must have the right tricks that can encourage the success of the company's goals. Human resources are the key to this success. This purpose of experience is the effect of culture, environment, and leadership at PT. Cahaya Bumi Nasional Surakarta. The research approach used is descriptive quantitative. This study used primary and secondary data. Non-probability sampling was applied in this with a saturated sample method of 50 respondents. The counting is multiple linear regression. The results is work culture t calculated = 2.444 > t in the table = 1.679, in the environment it is known that the calculated t = 2.043 > t in the table = 1.679, in leadership it is known that the calculated t = 2.009 > t in the table = 1,679, so conclusions are drawn is work culture, work environment, and leadership have a significant and positive effect on the work ethic at PT. Cahaya Bumi Nasional Surakarta. Keywords: Work Ehos,Work Culture,Work Environment, Leadership.